Aggregation platform for wind-pv-thermal technologies in electricity market - Gomes, Isaías (2019)
This paper addresses a stochastic Wind-PVThermal commitment to improve the bidding process of an aggregator in an electricity day-ahead market. The data for the wind and solar powers and for the market prices are given by a set of scenarios. Thermal units modeling includes start-up costs, variables costs and bounds due to constraints of technical operation, such as: ramp up/down limits and minimum up/down time limits. The modeling is carried out in order to develop a management aggregation procedure based in a stochastic programming approach formulated as a mixed integer linear mathematical programming problem. A case study is addressed with market price from the Iberian Peninsula and comparison between disaggregated and aggregated bids is discussed to address the main conclusions.